Determinan Harga Saham Sektor Properti Dan Realestat Di Bursa Efek Indonesia - Nuryasman MN; Yessica Yessica (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
Thisstudyaimstoexaminetheeffectofexchangerate(USD/IDR),inflationandBIRatetorealestateandpropertystockthatlistedinBEIfromJ a n u a r y2010–December2015with34samples.StatisticalanalysistoolusedwasEviews6withthepanelregressionanalysisandpurposivesamplingmethod.This study shows that togetherthe USD / IDR exchange rate, inflation rate and SBI interest rate significantly influencethe stock price. While partially only exchange rate USD / IDR and SBI interest ratewhichhave significant effect to stock price.